The Functionality of National Examinations Council Senior School Certificate Physics Practical Examination Items - Adediwura, Alaba Adeyemi; Adeoye, Oluseyi Peter (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
The study determined how the Senior School Certificate (S.S.C.) Physics Practical NECO examination items function differentially between male and female students and estimated the differential item functioning of the S.S.C. Physics Practical test items based on school type. It also ascertained the functionality of S.S.C. Physics Practical examination items between rural and urban dweller students. The research design adopted in this study was the descriptive survey research design. The population for the study was made up of all Senior Secondary Three (SS III) Physics students of Osun State in the 2017/2018 academic session—a total of 631 students selected through a multistage sampling procedure made up the sample. The NECO 2018 S.S.C. physics practical examination items were used to collect relevant data for the study. The chi-square likelihood ratio DIF method was adopted, and the mirt package was used for the analysis of collected data. The results showed that the proportion of DIF detected in the S.S.C. Physics practical examination under consideration was 8% (3 items) for sex, 5.4% (2 items) for type school and 32.4% (12 items) for school location. The study concluded that NECO physics practical examination items flagged moderately high incidence DIF with the location of the students. It is, therefore, recommended that NECO and other examination bodies that conduct such practical test needs to be conscious of students' location during test construction.